Cutting Edge Advancements in Management of Neovascular Age-Related Macular Degeneration A Scoping Review on Gene Therapy - Diannisa Paramita Susantono; Andi Arus Victor (Indonesian Vitreoretinal Society, 2026)
Introduction: Age-related macular degeneration (AMD) is the fourth leading cause of blindness globally. Therapeutic strategies for neovascular AMD (nAMD) have utilized anti-VEGF proteins, however compliance has become an issue. This study aims to explore current development on gene therapy as a new therapeutic strategy for nAMD to counter challenges in therapeutic compliance. Methods: A scoping review was conducted in May 2025, with articles obtained from Pubmed, Google scholar, Scopus, and Cochrane. Studies included were limited to systematic reviews and meta-analysis, randomized control studies, non-randomized controlled studies, and observational studies. Results: Three studies were reviewed, in which gene therapy for nAMD were conducted using different sets of transgenes and viral vectors, including RGX-314, ixoberogene soroparvovec, and rAAV.sFLT-1. Studies evaluated efficacy and safety, which mostly included visual acuity, central retinal thickness, recombinant protein concentration, and annualised injection rate. Duration of follow up among studies ranged from 2-3 years. Conclusion: The use of gene therapy in nAMD using RGX-314, ixoberogene soroparvovec, and rAAV.sFLT-1 is safe and tolerable. Differences among studies are associated with different transgenes and viral vectors. Current studies are on-going and awaiting results to potentially revolutionize the field of therapy in nAMD. Keywords: gene therapy, neovascular age related macular degeneration, wet age related macular degeneration, exudative age related macular degeneration, nAMD